2020
DOI: 10.1097/mpa.0000000000001500
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Capecitabine/Temozolomide for Locally Advanced or Metastatic Pancreatic Neuroendocrine Tumors

Abstract: Objectives The combination chemotherapy regimen capecitabine/temozolomide (CAPTEM) is efficacious for metastatic well-differentiated pancreatic neuroendocrine tumors (PNETs), but its role in the neoadjuvant setting has not been established. Methods The outcomes of all patients with locally advanced or resectable metastatic PNETs who were treated with neoadjuvant CAPTEM between 2009 and 2017 at 2 high-volume institutions were retrospectively reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“… 15 Another one‐arm study involving 30 patients with locally advanced or resectable metastases who received capecitabine or temozolomide chemotherapy illustrated patient prognoses after administration of chemotherapy, although four patients could not undergo surgery. 16 Another study involving 67 patients with liver metastases who underwent R0/1 surgeries illustrated the prognoses of 27 and 40 patients who received FAS therapy followed by surgery compared with surgery alone, respectively. 17 The present study involved 106 Pan‐NEN patients with locally advanced and/or liver metastases who were administered sunitinib and reported the prognosis of 31 patients who underwent surgery following sunitinib and 75 patients who did not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 15 Another one‐arm study involving 30 patients with locally advanced or resectable metastases who received capecitabine or temozolomide chemotherapy illustrated patient prognoses after administration of chemotherapy, although four patients could not undergo surgery. 16 Another study involving 67 patients with liver metastases who underwent R0/1 surgeries illustrated the prognoses of 27 and 40 patients who received FAS therapy followed by surgery compared with surgery alone, respectively. 17 The present study involved 106 Pan‐NEN patients with locally advanced and/or liver metastases who were administered sunitinib and reported the prognosis of 31 patients who underwent surgery following sunitinib and 75 patients who did not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The median Ki-67 index was 12% and mitosis was 2/10 HPFs, and the surgical indications for each type of liver metastases were similar to those reported in previous studies that illustrated neoadjuvant chemotherapy for Pan-NEN. [15][16][17] With the background data, the 5-y OS of the resected and nonresected groups were 89% and 14%, respectively (Figure 2). Thus, the present study demonstrated that patients who underwent surgery after sunitinib treatment had much better 5-y OS rates than those who did not undergo surgery (P < .001), although previous studies on aggressive surgery for advanced or metastatic Pan-NENs without preoperative chemotherapy indicated that the 5-y OS rates were 60-80%.…”
Section: F I G U R Ementioning
confidence: 94%
See 2 more Smart Citations
“…Pre-operative 5-fluorouracil, doxorubicin and streptozocin regimen has been associated with improved OS compared to surgery alone among patients with advanced synchronous pancreatic NELM (1). The orally-available regimen capecitabine and temozolomide (CAPTEM) is associated with favorable radiographic objective response rates for locally advanced or metastatic pancreatic NENs and may facilitate selection of patients appropriate for surgical resection (6). For what matters the potential role of PRRT in the neoadjuvant setting little is known in the specific context of NELM.…”
mentioning
confidence: 99%